Age-Related Deterioration of Mitochondrial Function in the Intestine. (19th August 2020) - Schneider, Anna M.; Özsoy, Mihriban; Zimmermann, Franz A.; Feichtinger, René G.; Mayr, Johannes A.; Kofler, Barbara; Sperl, Wolfgang; Weghuber, Daniel; Mörwald, Katharina
Abstract : Aging is an important and inevitable biological process in human life, associated with the onset of chronic disease and death. The mechanisms behind aging remain unclear. However, changes in mitochondrial function and structure, including reduced activity of the mitochondrial respiratory chain and increased production of reactive oxygen species—thus oxidative damage—are believed to play a major role. Mitochondria are the main source of cellular energy, producing adenosine triphosphate (ATP) via oxidative phosphorylation. Accumulation of damaged cellular components reduces a body's capacity to preserve tissue homeostasis and affects biological aging and all age-related chronic conditions. This includes the onset and progression of classic degenerative diseases such as cardiovascular disease, kidney failure, neurodegenerative diseases, and cancer. Clinical manifestations of intestinal disorders, such as mucosal barrier dysfunction, intestinal dysmotility, and chronic obstipation, are highly prevalent in the elderly population and have been shown to be associated with an age-dependent decline of mitochondrial function. This review summarizes our current understanding of the role of mitochondrial dysfunction in intestinal aging.